Game-Based Learning for the Digital Age: A Narrative Review across Educational Levels - Usman, Asep Tutun; Anisah, Ani Siti; Marwah, Sopa Siti; Holis, Ade (Yayasan Sinergi Kawula Muda, 2025)
This narrative review investigates the effectiveness of gamification in improving student engagement and academic performance across educational levels. The study aims to explore how gamified learning environments influence cognitive, behavioral, and emotional aspects of learning. A structured narrative methodology was employed, synthesizing empirical evidence from global studies, including quantitative and qualitative data, to identify key themes and trends in gamified education. Findings indicate that gamification significantly enhances student engagement, participation, and learning outcomes through the use of points, badges, leaderboards, and real-time feedback. These elements align with classical learning theories such as behaviorism and constructivism, and when designed in accordance with self-determination principles, promote intrinsic motivation and learner autonomy. The integration of gamification is particularly effective when adapted to students' cognitive development levels, demonstrating differentiated impact across primary, secondary, and tertiary education. However, systemic challenges such as infrastructure limitations, teacher preparedness, and policy gaps hinder optimal implementation. The discussion emphasizes the need for comprehensive policy support, investment in digital infrastructure, and professional development for educators. The study concludes that gamification is a powerful pedagogical approach when applied strategically, offering a transformative path toward inclusive, interactive, and effective education.